Analisis tipe kepemimpinan profetik Kepala Perpustakaan Universitas Muhammadiyah Yogyakarta - Ifonilla Yenianti (IJAL (Indonesian Journal of Academic Librarianship), 2022)
Head of the Library of Muhammadiyah University (UMY), as well as the author of books about library management, namely Lasa H.S. is a teacher, father, and role model for future librarians. His peak career as the main librarian became his extraordinary dedication at the Library of Gadjah Mada University (UGM) Yogyakarta. Lasa H.S.'s motivational quotes namely "If you want to know the world then read and if you want to be known by the world then write". After his retirement at UGM, he was asked by UMY to become a Captain at the UGM Library. Armed with his experience while serving at the UGM Library, he got the mandate to be the Head of the UMY Library for three periods. The focus of this research is on the type of leadership of the Head of the UMY Library. The types of prophetic leadership include authoritarian leadership, Laissez Faire leadership, and democratic leadership. This study uses a qualitative descriptive method using data from interviews, literature studies and documentation. The informants of this study were the head of the UMY library and librarian. The result of this research is that Lasa H.S. in carrying out his leadership duties at the UGM library, he is a type of prophetic leadership based on Islam and guided by the Koran and Hadith. This prophetic leadership is included in situational leadership theory, which combines several leadership models, namely: authoritarian, laissez faire, and democratic.